2012
DOI: 10.1111/j.1745-8315.2012.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding alexithymia within a psychoanalytical framework

Abstract: The object of this paper is to provide a metapsychological definition of alexithymia as described in 1967 in terms of operational thinking and negative hallucination. This is a familiar and established concept in the fields of psychopathology, psychology, and of clinical and psychosomatic medicine. From a psychoanalytic and psychosomatic point of view, the term is conceptually close to P. Marty's "operative thinking", as described in 1963, even though we know they do not belong to the same epistemological fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Meanwhile, depression seems to be related to nonresponses, especially at negative cues, suggesting the hypothesis of an additional inhibitory effect played by mood disorders in AN adolescent subjects. Similarly, although alexithymia might play a role in altering AM (Pirlot & Corcos, 2012), and could contribute to the emotional dysregulation observed in ED, our findings showed that it cannot per se account for overgeneralization. From this point of view, our data are in accordance with literature on adult women with AN (Nandrino et al, 2006).…”
Section: Discussionmentioning
confidence: 52%
“…Meanwhile, depression seems to be related to nonresponses, especially at negative cues, suggesting the hypothesis of an additional inhibitory effect played by mood disorders in AN adolescent subjects. Similarly, although alexithymia might play a role in altering AM (Pirlot & Corcos, 2012), and could contribute to the emotional dysregulation observed in ED, our findings showed that it cannot per se account for overgeneralization. From this point of view, our data are in accordance with literature on adult women with AN (Nandrino et al, 2006).…”
Section: Discussionmentioning
confidence: 52%
“…His speech continues to be very focused upon the current and the factual, with difficulties in providing associations of any relevance; his oneiric activity is very limited, and when dreams do appear they are often mere reproductions of waking experiences, with little process of elaboration. This is reminiscent of the operational‐life‐type functioning of the Paris School (Marty and De M'Uzan, ; Pirlot and Corcos, ), which certain authors have also described for other types of non‐neurotic cases such as borderline patients (Braier, ).…”
Section: Discussion Of the Clinical Facts Presented In The Patient's mentioning
confidence: 84%
“…Je comprends mieux comment cela arrive, je suis occupée à une tâche, ou suis "dans ma tête" et, soudainement, quelqu'un entre dans mon bureau, me parle ou alors, comme lorsque j'étais rentrée chez moi en pensant être seule, je dois, brutalement, m'adapter à un nouvel environnement alors que je ne suis pas prête à cela ». Tout au long de cette analyse en face à face, je percevais chez elle un mode opératoire ou alexithymique de pensée (Pirlot et Corcos, [37]). Elle cherchait des mots pour décrire ses émotions, celles-ci ne s'exprimant que sous forme de sensations.…”
Section: Désubjectivation Et Quête Subjective : Catherineunclassified